2021
DOI: 10.1097/pas.0000000000001843
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mucosal Eosinophils for the Histopathologic Diagnosis of Eosinophilic Gastritis and Duodenitis

Abstract: Eosinophilic gastrointestinal diseases, specifically eosinophilic gastritis and duodenitis, are chronic inflammatory conditions characterized by persistent gastrointestinal (GI) symptoms and elevated levels of activated eosinophils in the GI tract. Both clinical and endoscopic findings are nonspecific, no clinical or histopathologic diagnostic guidelines are published, and disease awareness is low, both among clinicians and amongst pathologists, who tend to overlook mild or moderate increases in the density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
1
27
0
4
Order By: Relevance
“…According to the criteria proposed by Talley et al, the diagnosis of EoG should be based on both clinical symptoms and histological evidence of significant gastric eosinophilia (>30 eosinophils/5 high power fields, hpf) in the gastric antrum and/or body, whereas endoscopic findings are not essential (16). Although the number of 30 eosinophils/hpf as the upper limit of normal for stomach and duodenum has been proposed, others have suggested lower or higher thresholds (18). Given the patchy nature of EoG, multiple random biopsies are warranted per site (at least 5-6 biopsies) (19).…”
Section: Eosinophilic Gastritismentioning
confidence: 99%
“…According to the criteria proposed by Talley et al, the diagnosis of EoG should be based on both clinical symptoms and histological evidence of significant gastric eosinophilia (>30 eosinophils/5 high power fields, hpf) in the gastric antrum and/or body, whereas endoscopic findings are not essential (16). Although the number of 30 eosinophils/hpf as the upper limit of normal for stomach and duodenum has been proposed, others have suggested lower or higher thresholds (18). Given the patchy nature of EoG, multiple random biopsies are warranted per site (at least 5-6 biopsies) (19).…”
Section: Eosinophilic Gastritismentioning
confidence: 99%
“…This pathologist reported a count of 30 or more eosinophils per high‐power field in several gastric biopsies, but then concluded that ‘the number is not sufficient to warrant a diagnosis of eosinophilic gastritis’, even though some would recommend this level for diagnosis. However, in the absence of consensus guidelines, it remains a matter of different opinions 35,36 . One question emerging from these analyses is whether insufficient biopsy sampling could be partially responsible for the low numbers of histopathologic diagnoses of non‐oesophageal EGIDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of consensus guidelines, it remains a matter of different opinions. 35,36 One question emerging from these analyses is whether insufficient biopsy sampling could be partially responsible for the low numbers of histopathologic diagnoses of non-oesophageal EGIDs. Since eosinophilia in the gastrointestinal tract is patchy, could the lack of adequate sampling have hindered the detection of EGIDs?…”
Section: Discussionmentioning
confidence: 99%
“…4 Diagnosis of EGIDs is further challenged due to lack of guidelines for histopathologic criteria. 5,6 Another reason for misdiagnosis could be inadequate communication by the endoscopist to the pathologist on suspicion of EGID.…”
Section: N V I T E D E D I T O R I a L Editorial: The Cta On Egidsmentioning
confidence: 99%
“…In one study, there was a mean of 3.6 years from symptoms to diagnosis, and missed diagnosis on index endoscopy in 38.2% of patients 4 . Diagnosis of EGIDs is further challenged due to lack of guidelines for histopathologic criteria 5,6 …”
mentioning
confidence: 99%